Role of contextual and individual factors in early foreign language learning - Mihaljević Djigunović, Jelena (2011)
Early foreign language (FL) learning is becoming an increasingly common phenomenon across the world. Research into early FL acquisition processes and outcomes are of key importance now because in many contexts unrealistic aims and expectations are set by policy makers as well as parents (Nikolov and Mihaljević Djigunović 2006, 2011). A sample of 172 Croatian L1 beginners (aged 6-7 years) learning English as a foreign language (EFL) was followed for four years. They were drawn from metropolitan, small town and rural schools. Data on the broader learning context and the immediate learning environment was gathered by means of interviews with EFL teachers and school principals, parents questionnaires and classroom observation. Information on individual learner characteristics was collected by smiley questionnaires and oral interviews with the young learners administered each year. FL development over the years was measured by means of listening and speaking tasks. Such tasks were used because oracy is the main focus in the beginning years of early FL learning: listening and speaking provide the basic input for literacy development in young FL learners. It is through oral language that the foundation for learning a new language is established. Aural comprehension and oral production thus emerge as language skills that best enable young learners to learn. Listening comprehension was measured by means of two types of tasks: multiple choice items accompanied with three pictures, and true/false statements about one complex picture. The tasks measured the ability to identify specific vocabulary items as well as comprehension of short chunks supported by visuals. Data on oral production was collected by means of two oral tasks: a simulation task and an interactive task (a guess who game). These were used to elicit participants' language in terms of lexical diversity and syntactic complexity. Results on language development were analysed taking into account data relating to contextual factors (teaching quality, exposure to English, home support, socio-economic status) and individual learner factors (attitudes, motivation, linguistic self-concept). Significant effects were found in case of both listening comprehension and oral production. Such results provide evidence for important roles that learner characteristics and the FL learning setting play in early acquisition of a FL. Overall, our findings suggest that early FL learning is a highly complex process. Its can be fully appreciated only if considered from all relevant perspectives. Once early FL programmes are based on a research-informed understanding of the processes involved in early language learning, their aims and expectations will probably become more realistic too.